Ethical considerations in emergency Medical services (EMS): understanding the significance of confidentiality (a scoping review) - Aung, Khin Thandar (2024)
Emergency Medical Services (EMS) play a critical role in the healthcare system, providing immediate care to individuals in life-threatening situations. The ethical principle of confidentiality, a cornerstone of healthcare that extends to prehospital care settings. This scoping review seeks to explore the importance of confidentiality in EMS, its ethical implications, and the factors influencing its application. A scoping review was conducted using the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. A literature search was conducted using electronic databases such as PubMed, Scopus, and Google Scholar. The search terms included “EMS,” “emergency medical services,” “confidentiality,” “ethics,” and “ethical considerations.” The inclusion criteria for this review were empirical studies, review articles, and ethical considerations in EMS and confidentiality-related guidelines.